2007
DOI: 10.1172/jci32430
|View full text |Cite
|
Sign up to set email alerts
|

Senescence regulates macrophage activation and angiogenic fate at sites of tissue injury in mice

Abstract: Abnormal angiogenesis plays a key role in diseases of aging such as heart disease, certain cancers, and eye diseases including age-related macular degeneration. Macrophages have been shown previously to be both anti-and proangiogenic, and their role in regulating angiogenesis at sites of tissue injury is critical and complex. In this study, we analyzed cytokine gene expression patterns of mouse macrophages by realtime quantitative PCR and tested the functional effects of senescence on gene expression and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
214
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(228 citation statements)
references
References 15 publications
10
214
3
1
Order By: Relevance
“…Macrophages can exhibit both proand antiangiogenic functions based largely on their polarization by cytokines in the resident tissue microenvironment (71). Of these cytokines, IL-10 may possess the most significant influence on the polarization of macrophages and their ability to regulate angiogenesis in the eye (72). Low levels of IL-10, which is a characteristic feature of the retinal environment of miR-155 Ϫ/Ϫ mice after OIR, are associated with "classically activated" macrophage, or M1 macrophage, that displays an antiangiogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages can exhibit both proand antiangiogenic functions based largely on their polarization by cytokines in the resident tissue microenvironment (71). Of these cytokines, IL-10 may possess the most significant influence on the polarization of macrophages and their ability to regulate angiogenesis in the eye (72). Low levels of IL-10, which is a characteristic feature of the retinal environment of miR-155 Ϫ/Ϫ mice after OIR, are associated with "classically activated" macrophage, or M1 macrophage, that displays an antiangiogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, peripheral macrophages exhibited less classical activation, leading to an attenuated proinflammatory response [207]. In a mouse model of age-related macular degeneration, ocular macrophages from old mice exhibited increased IL-10 but decreased IL-12 and TNF-α, suggesting that aged macrophages are polarized toward an M2-like phenotype [208]. Another study also reported increased numbers of M2 macrophages in the spleen, lymph nodes, and bone marrow of aged mice [209].…”
Section: Agingmentioning
confidence: 99%
“…To further investigate the role of EC FGFR1/2 in vascular response to injury, we examined vascular response to choroidal injury and retina hypoxia. Laser-induced choroidal neovascularization (CNV) is well described as a proliferative neovascular response to injury to the retinal pigment epithelium and Bruch's membrane underneath the retina and a murine surrogate for the wet form of age-related macular degeneration (33,34). Following choroidal injury, DCKO mice showed a marked reduction in CNV compared with control Flk1-Cre or Tie2-Cre and DFF mice, as determined by quantifying FITC-dextran-perfused neovascular complexes overlying the injury site (Fig.…”
Section: Endothelial Fgfr1/2 Is Required For Neovascular Response Inmentioning
confidence: 99%